The Influence of Material Quality and Project Management on the Risk of Building Construction Delays - Tri Satriawansyah; Apra Santosa, Tomi (AKADEMI TEKNIK ADI KARYA, 2025)
Construction delays remain a critical issue in building projects, as they often lead to cost overruns, reduced quality, and disputes among project stakeholders. Among the various contributing factors, material quality and project management practices are frequently identified as dominant determinants influencing project performance. This study aims to analyze the influence of material quality and project management on the risk of delays in building construction projects. A quantitative research approach was employed using a survey method involving contractors, project managers, and site engineers engaged in building construction projects. Data were collected through structured questionnaires and analyzed using multiple linear regression techniques to examine both partial and simultaneous effects of the independent variables on construction delay risk. The analysis results indicate that material quality has a significant negative effect on the risk of construction delays, implying that higher-quality materials reduce the likelihood of project setbacks. Furthermore, effective project management demonstrates a strong and significant influence in minimizing delay risks through improved planning, coordination, and control mechanisms. Simultaneously, material quality and project management were found to have a substantial combined effect on reducing construction delay risks. These findings highlight the importance of integrating rigorous material quality control with professional project management practices to enhance schedule reliability in building construction projects. The study provides practical implications for construction stakeholders in developing proactive strategies to mitigate delay risks and improve overall project performance.